FREQUENCY OF LOSS OF MISMATCH REPAIR PROTEINS’ IMMUNOHISTOCHEMICAL EXPRESSION IN SEBACEOUS NEOPLASMS, POTENTIAL MARKERS/TOOLS INDICATING THE POSSIBILITY OF MUIR-TORRE SYNDROME - QURESHI, R; FATIMA, S (Biological and Clinical Sciences Research Journal, 2024)
Screening for Muir-Torre Syndrome (MTS) using Mismatch Repair (MMR) gene immunohistochemistry (IHC) on sebaceous neoplasms (SNs) is technically feasible. Research for this indication is limited, especially in Asia. To address this knowledge gap, we examined the frequency of loss of IHC staining of MMR proteins in SNs. Methods: We conducted a cross-sectional study including 98 patients (120 SNs). Eleven out of 98 patients had concurrent or subsequent SNs. Results: The size and type of tumor showed a significant association with MMR loss. Fifteen (12.5%) sebaceous adenomas, 12 (10.0%) sebaceous, and 93 (77.5%) sebaceous carcinomas were included in the study—sixty-one (50.83 %) SNs presented with loss of one or more MMR proteins. Isolated loss of MSH2 was the most common IHC pattern (27.8%). Fifty cases (29.58%) showed a combined loss of MSH2 and MSH6, and 40 (23.66%) showed a combined loss of MLH1 and PMS2. Most SAs showed isolated loss of MLH1 and PMS2 (7, 26.9% each). Sebaceomas showed isolated loss of MSH2 and MSH6 as the most common (4, 33.3%) pattern. Isolated loss of MSH2 only (37, 28.2%) was the predominant pattern of IHC loss in SCs. Weak to fragile associations between MMR protein status and histopathological findings were observed, with the most notable association being between MLH1 and ulceration on the surface. The models have an accuracy of around 50%, indicating moderate prediction capability. In our cohort, personal and family history was available in 33 cases (25 out of 98 patients). Conclusion: We recommend that MMR IHC be performed routinely on all SNs, considering clinicopathological factors of the lesions, mainly the anatomic site and tumor type. The panel should include antibodies against all four MMR proteins.